Downey, Leah. Our Money: Monetary Policy as if Democracy Matters - Raskin, Sarah Bloom (Journal of Economic Literature, 2025)
Sarah Bloom Raskin of Colin W. Brown Distinguished Professor of Practice, Duke University School of Law reviews “Our Money: Monetary Policy as if Democracy Matters” by Leah Downey. The Econlit abstract of this book begins: “Explores how decisions about who gets to decide if, when, and on what terms money is created influence the possibilities for collective self-government, investigating the institutional arrangements that determine who makes these choices.”